Religiosity of Children Preparing for the First Holy Communion. An Empirical Study - Mikołajczak, Sylwia (Studia Warmińskie, 2024)
The article presents the results of an empirical study on the religiosity of children preparing for their first Holy Communion. The study examined, among other things, their regularity and motivation for attending Sunday Mass, daily prayer, religious practices, as well as the reasons why students want to receive the Lord Jesus in the sacrament of the Eucharist. The research was carried out by a diagnostic survey method, using a questionnaire technique. The research tool used to gather data was a survey questionnaire, consisting of fifteen questions. On the basis of it, 81 third-grade students of Elementary School No. 12 in Olsztyn, attending religious instruction and preparing to receive their first Holy Communion, were surveyed. The collected research material made it possible to conclude that the majority of respondents regularly attend Sunday Mass, and the motivation for going to church is the desire to meet the Lord Jesus. However, the company’s own research shows that students who declare regular prayer or reading of the Holy Scriptures - constitute a minority of the surveyed sample.